Counselling students with hearing impairment and their parents: implications for professional practice (2015)
Counselling is a vital tool for assisting children with hearing impairment and their parents to adjust to their environment. This paper focused on counselling students with hearing impairment and their parents: Implications for professional practice. The author examined the meaning of counselling, the roles of counsellors of students with hearing impairment and their parents, qualities of counsellors, parents' initial reactions to having a child with disability in the family and the need for counsellors' intervention and rationale for counselling students with hearing impairment and their parents. Recommendations were made based on the observations made by the author.